1984
DOI: 10.1016/0048-9697(84)90241-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of soot and primary oxidants in atmospheric chemistry

Abstract: This paper discusses the role of soot in atmospheric sulfur chemistry. A methodology for estimating the primary and secondary particulate carbon concentrations is outlined. The relationship between ambient S02, sulfate, and primary carbon is examined; and certain regularities in their behavior are defined. An explanation of these regularities is proposed, based on a mechanism involving oxygen chemisorbed on combustion-generated carbon particles and its subsequent reaction with aqueous sulfite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 9 publications
1
46
0
Order By: Relevance
“…From the evidence presented so far, we are inclined to hypothesize that the rapid S0 2 oxidation observed in the morning period is caused by incomplete combustion products in the presence of liquid water droplets (Brodzinsky et al, 1980;Chang et al, 1981;Novakov, 1984;Benner et al, 1985). Field evidence supporting this hypothesis was obtained by Eatough et al (1984), who observed rapid sulfate formation when the plume of an oil-burning power plant impacted on a fog bank.…”
Section: Resultsmentioning
confidence: 69%
“…From the evidence presented so far, we are inclined to hypothesize that the rapid S0 2 oxidation observed in the morning period is caused by incomplete combustion products in the presence of liquid water droplets (Brodzinsky et al, 1980;Chang et al, 1981;Novakov, 1984;Benner et al, 1985). Field evidence supporting this hypothesis was obtained by Eatough et al (1984), who observed rapid sulfate formation when the plume of an oil-burning power plant impacted on a fog bank.…”
Section: Resultsmentioning
confidence: 69%
“…There is an effort within the community, however, to use these terms more precisely in the future (Schauer et al, 2003). The developing convention is to use BC as the definition of optical measurements of light-absorbing carbon (Novakov, 1984;Goldberg, 1985) and EC as the definition of refractory carbon measured by thermal/optical carbon analyzers. The term Carbon Black should only be used to describe the commercially produced commodity that is used in the rubber, painting and printing industries (Watson and Valberg, 2001).…”
Section: Measurements Of Ecmentioning
confidence: 99%
“…Most common carbon-specific methods consist of combined thermal and gas-analytical approaches based on the analysis of gasification products evolving from a heated filter sample (Malissa et al, 1976;Puxbaum, 1979;Gundel et al, 1981;Novakov, 1984). These methods make use of the thermal resistivity of the "elemental carbon" fraction of carbonaceous matter, which does not volatilize in an inert atmosphere at temperatures as high as 4000 K. It can only be gasified by oxidation starting at temperatures above 340 • C (Cachier et al, 1989;Jennings et al, 1994).…”
Section: Evolved Carbonmentioning
confidence: 99%
“…It states in the first paragraph "The term 'black carbon' is used in this paper to refer to the optically absorbing carbonaceous component of ambient and source aerosols." Based on the pioneering work of Novakov (1984), Goldberg (1985) and Shah and Rau (1990), the following analytically based definitions have been introduced since then:…”
Section: Historic Definitionmentioning
confidence: 99%